2012
DOI: 10.1039/c1dt11678a
|View full text |Cite
|
Sign up to set email alerts
|

Allylic alcohols as synthetic enolate equivalents: Isomerisation and tandem reactions catalysed by transition metal complexes

Abstract: Allylic alcohols can be isomerised into carbonyl compounds by transition metal complexes. In the last few years, catalyst design and development have resulted in highly efficient isomerisations under mild reaction conditions, including enantioselective versions. In addition, the isomerisation of allylic alcohols has been combined with C-C bond forming reactions when electrophiles such as aldehydes or imines were present in the reaction mixture. Also, C-F bonds can be formed when electrophilic fluorinating reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
81
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(82 citation statements)
references
References 112 publications
0
81
0
1
Order By: Relevance
“…Nevertheless, hydride donors such as H2, 2-propanol or aqueous formate can facilitate the formation of the catalytically active hydrido species. [47] Dcalc/Mg m Under hydrogen the reaction catalyzed by 1 led to a highly selective conversion of 1-octen-3-ol (in 1 h, TOF = 42 h -1 ) to octan-3-one (83 %) with only 2 % of the hydrogenated product, octan-3-ol (Scheme 3). This result demonstrates for the first time, that in a dihydrogen atmosphere 1 can be successfully used for redox isomerization of 1-octen-3-ol under mild conditions with high activity and selectivity to octan-3-one.…”
Section: Isomerization Of Allylic Alcohols Catalyzed By Ru(ii)-dmso Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, hydride donors such as H2, 2-propanol or aqueous formate can facilitate the formation of the catalytically active hydrido species. [47] Dcalc/Mg m Under hydrogen the reaction catalyzed by 1 led to a highly selective conversion of 1-octen-3-ol (in 1 h, TOF = 42 h -1 ) to octan-3-one (83 %) with only 2 % of the hydrogenated product, octan-3-ol (Scheme 3). This result demonstrates for the first time, that in a dihydrogen atmosphere 1 can be successfully used for redox isomerization of 1-octen-3-ol under mild conditions with high activity and selectivity to octan-3-one.…”
Section: Isomerization Of Allylic Alcohols Catalyzed By Ru(ii)-dmso Cmentioning
confidence: 99%
“…[29,[47][48][49] cis-[RuCl2(dmso)4] has already been applied as catalyst for isomerization of 3-buten-2-ol to butan-2-one in homogeneous water-diglyme solvent mixtures, however, as high temperatures as 130 °C had to be used for meaningful reaction rates. [31] Gimeno et al studied the reduction of 1-octen-3-ol by hydrogen transfer from 2-propanol with 1 as catalyst in homogeneous solution.…”
Section: Isomerization Of Allylic Alcohols Catalyzed By Ru(ii)-dmso Cmentioning
confidence: 99%
“…[14] Previous studies support that the formation of a-functionalized carbonyl compounds from allylic alcohols occurs through: 1) a transition-metal-catalyzed 1,3-hydrogen shift forming an enolate or an enol intermediate, and 2) subsequent nucleophilic attack on the electrophile (Scheme 4). [6][7][8][9] In a cross-over experiment using deuterium-labeled [D 1 ]-2 f, we have confirmed that the isomerization follows an intramolecular 1,3-hydrogen shift (Scheme 5 and the Supporting Information). [7b, 8] Although this result is consistent with the intermediacy of enol(ate)s, the details of the mechanism, and in particular of the C À Cl bond formation step, remain to be elucidated.…”
mentioning
confidence: 63%
“…A considerable advantage of using allylic alcohols as enol equivalents [6,7] is that the new bond (to the electrophile) is formed exclusively at the alkenylic carbon atom of the allylic alcohol [RCH(OH) À CH = CHR; Scheme 1b]. This type of transformation has almost exclusively been investigated using carbon electrophiles (e.g.…”
mentioning
confidence: 99%
“…5,6 This method yields the products in a single synthetic step through a formal 1,3-hydrogen shi. [5][6][7] Great advances have been made in this area of research in the past decade using simple substrates. [8][9][10] Applying the transition metal-catalyzed redox isomerization reaction to synthesize semi-synthetic opiate drugs requires overcoming important challenges.…”
mentioning
confidence: 99%